2018
DOI: 10.1021/acsami.8b03776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humidity and Water Intercalation on the Tribological Behavior of Graphene and Graphene Oxide

Abstract: In this work, the effect of humidity and water intercalation on the friction and wear behavior of few-layers of graphene and graphene oxide (GO) was studied using friction force microscopy. Thickness measurements demonstrated significant water intercalation within GO affecting its surface topography (roughness and protrusions), whereas negligible water intercalation of graphene was observed. It was found that water intercalation in GO contributed to wearing of layers at a relative humidity as low as ∼30%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 52 publications
5
71
0
Order By: Relevance
“…[11] While there is some understanding of mechanisms (localized interlayer shearing, puckering effect, electron phonon coupling etc.) at the nanoscale associated with water influencing friction for graphene, graphene oxide (GO) and graphite edges [15][16][17][18][19][20][21][22][23][24] , there is only limited understanding for MoS2 and oxidized-MoS2 at the nano/molecular scale. Advancement of technological tools such as the atomic force microscope (AFM)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] While there is some understanding of mechanisms (localized interlayer shearing, puckering effect, electron phonon coupling etc.) at the nanoscale associated with water influencing friction for graphene, graphene oxide (GO) and graphite edges [15][16][17][18][19][20][21][22][23][24] , there is only limited understanding for MoS2 and oxidized-MoS2 at the nano/molecular scale. Advancement of technological tools such as the atomic force microscope (AFM)…”
Section: Introductionmentioning
confidence: 99%
“…has allowed studying the fundamental mechanisms governing friction at atomic/molecular scale. [17,18,25,26] In particular, recent advancements for controlling the environment locally around the single AFM contact have expanded our understanding, by moving away from studying friction as a function of normal load only to consider the role of other variables such as relative humidity [15] and temperature. [27,28] At the atomic scale, MoS2 is categorized as a 2D transition metal dichalcogenide (TMD), consisting of a covalently bonded tri-layer structure, with molybdenum atoms sandwiched between sulfur atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, the related adsorbent materials should possess a high affinity to H 2 O with low energy costs associated with the activation, regeneration, and recycling. Much efforts then have been devoted to the design and preparation of such materials . Zeolites 3A, 4A, 5A, 13X, silica gel, and activated alumina are the well‐known dehydrating agents for the aforementioned purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites 3A, 4A, 5A, 13X, silica gel, and activated alumina are the well‐known dehydrating agents for the aforementioned purpose. However, none of them belongs to the ideal candidate due to a relatively low uptake amount or energy‐intensive regeneration steps . More recently, Cadiau et al have demonstrated that the fluorinated MOFs NiAlF 5 (H 2 O) (pyrazine) 2 ·2(H 2 O) and NiFeF 5 (H 2 O)(pyrazine) 2 ·4(H 2 O) can selectively remove water vapor from industrial gas streams with moderate energy input for regeneration, thus emerging as one of strong competitors for commonly used desiccants.…”
Section: Introductionmentioning
confidence: 99%